Worker Protection Standard: Requirements for Commercial Pesticide Handler Employers - Frederick M. Fishel (EDIS, 2018)
In 1992, the US Environmental Protection Agency issued a comprehensive regulation called the Worker Protection Standard for Agricultural Pesticides (WPS). The EPA has made several changes to the WPS since it was fully implemented in 1995. This 5-page document will address the WPS protections commercial pesticide handler employers must provide to their handlers. Written by Frederick M. Fishel and published by the UF/IFAS Agronomy Department, January 2018. http://edis.ifas.ufl.edu/pi275